ANALISIS SYARAT ADMINISTRATIF PROSES PEWARGANEGARAAN DI INDONESIA DALAM PERSPEKTIF PELAYANAN PUBLIK - Efendi, Virga Dwi; Rizqi, Muhammad Fathur (Veritas et Justitia, 2024)
Indonesia’s citizenship system offers three distinct pathways for applicants, each with unique administrative processes. These variations impact the agencies involved, the associated costs, and the implementation of citizenship procedures. This research aims to examine the differences in administrative requirements within Indonesia’s citizenship framework from a public policy perspective, as outlined in Law Number 25 of 2009 concerning Public Services. The analysis employs a juridical-normative approach to explain the administrative prerequisites for obtaining Indonesian citizenship. The findings highlight the need for transformative measures under Law Number 12 of 2006 concerning Citizenship, particularly by enhancing coordination among ministries and agencies to deliver more effective and efficient citizenship services.